2018
DOI: 10.1371/journal.pone.0209959
|View full text |Cite
|
Sign up to set email alerts
|

Mothers treatment seeking intention for neonatal danger signs in northwest Ethiopia: A structural equation modeling

Abstract: BackgroundNeonatal mortality contributes to nearly half of under-five mortality in Ethiopia. Treatment seeking for newborn danger signs remains low despite correlations with neonatal mortality. This study tests a theoretical model of factors affecting mothers’ treatment seeking intention for neonatal danger signs in northwest Ethiopia.MethodA cross sectional study was conducted from March 3–18, 2016 in northwest Ethiopia. A total of 2,158 pregnant women and women who had delivered in the past 6 months were int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…sunlight), newborn isolation from strangers until the newborn has been religiously blessed and ambiguous newborn personhood [7,14,17]. However, only three known studies assess the determinants of care for sick newborns in Amhara [6,18,19] with no known studies assessing household care seeking for neonatal PSBI in the region. Although findings are specific to the woredas sampled in this study, recommendations may be transferable by local and regional contexts.…”
Section: Introductionmentioning
confidence: 99%
“…sunlight), newborn isolation from strangers until the newborn has been religiously blessed and ambiguous newborn personhood [7,14,17]. However, only three known studies assess the determinants of care for sick newborns in Amhara [6,18,19] with no known studies assessing household care seeking for neonatal PSBI in the region. Although findings are specific to the woredas sampled in this study, recommendations may be transferable by local and regional contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal mortality contributes to nearly half of the under-five mortality in Ethiopia [7]. Neonatal mortality declined from 49 deaths per 1,000 live births in 2000 to 29 deaths per 1,000 births in 2016, a reduction of 41% over the past 16 years [8].…”
Section: Introductionmentioning
confidence: 99%
“…In our conceptual model, neonatal danger sign knowledge was the most proximal factor to neonatal care-seeking; having only a direct effect on care-seeking (75)(76)(77)(78) and serving as a mediating channel for most factors to affect neonatal careseeking for illness episodes. Our study results showed low knowledge levels among women about danger signs.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence deems the importance of raising maternal awareness about newborn danger signs, most importantly, raising awareness regarding the severity and subsequent qualified care-seeking options. Counseling and health education should be strengthened at the available contact points during the antenatal, delivery, and postnatal periods at the facility and in the community ( 75 , 78 ).…”
Section: Discussionmentioning
confidence: 99%